METHODOLOGICAL ASPECTS OF TEACHING THE COURSE "SCIENTIFIC COMMUNICATION IN PROFESSIONAL ACTIVITY" FOR FUTURE SPECIALISTS - Lytvynska, Svitlana; Prykhodko, Oksana (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The course “Scientific communications in professional activity” (SCPA) plays an important role in the education of the specialists in various professional fields, forming competencies that are important for the labor market of the 21st century. Moreover, the analysis of methodological approaches and practical tasks, which find their embodiment in the discussed course, is important for improving the practical content, which will prepare and establish competitive professionals. The purpose of scientific research is to outline the methodological approaches and principles that form the basis of training students of higher education through the course “Scientific communications in professional activity”. Forms of practical work with applicants are defined and the manner in which the specific competencies of the course are integrated with competencies related to other educational programs of applicants have been characterized. The research involves the methods of content analysis, distributive analysis of linguistic material, general scientific methods (analysis, synthesis, systematization, generalization). Result. SCPA is an important component of the educational trajectory of modern students. It combines linguistic orientation with general skills in the project implementation, in which it is important to be able to represent one’s own achievements. The course is a relevant factor in the formation of ideas about the principles of work in the discourse of academic integrity, and at the same time it helps to effectively and qualitatively systematize the results of activities, to inform partner communities (donors, grant-makers, state institutions, etc.) about them in order to achieve the goals. SCPA outlines not only linguistic skills and business communication skills, but also provides an opportunity to look at work results from a detached and impartial perspective, identify strengths and weaknesses, better prepare for the dissemination of one’s ideas and gain support in the professional community. Conclusions. SCPA requires substantive differentiation depending on the educational direction of the applicants. It is important to adapt the content of SCPA to the practical needs and requests of the future specialists. During practical classes, it is necessary to move away from the project activity in order to help the applicants to improve their own work for its further presentation in the environment of partners, sponsors, etc. It is necessary to use contemporary methods aimed at strengthening the competitiveness of young people in the labor market. Tasks explicated in the content body of the course should correspond to contemporary knowledge paradigm of business, technology, economic and financial activity in today’s world and at the same time be adapted according to the direction of training. Therefore, SCPA is an important component of the contemporary educational trajectory, the content modules of which can incorporate tasks that are important for the formation of professionally successful young people who are able to effectively and efficiently present the results of their own project activities